The Effect of the Jumbo Snakes and Ladders Game Media on the Motor Development and Numeracy Ability of Kindergarten Children - Ami Ari Mami; Eges Triwahyuni; Kustiyowati (Jurnal Penelitian Pendidikan IPA, 2025)
The golden age of lifelong learning begins when children are between the ages of 0 and 6. The objectives of this research are to determine the effect of the giant snakes and ladders game media on children's motor development and counting skills at Nusa Indah Kindergarten, and to determine the effect of the giant snakes and ladders game media on children's counting skills at Nusa Indah Kindergarten. This study uses a quantitative approach with a quasi-experimental research design. The results of this study indicate that the learning outcomes of early childhood students in group B at Nusa Indah Kindergarten, through the jumbo snakes and ladders game model, can improve children's motor development. Second, the jumbo snakes and ladders game model can also improve the counting abilities of early childhood students.